Marketing strategy for computer services in Melaka area / Afzan Kuangit@Abdullah - Kuangit/Abdullah, Afzan (Faculty of Business and Management, 2002)
Strategic marketing is one of the factors that can contribute to the successful of an organization in selling their product or service. This research is carried out to find out the most appropriate marketing strategy for computer services in Melaka areas. The objectives to the studies are (1) To examine the strategic marketing that can be used to build customer loyalty. (2) To identify either the brand can influence customer's choice and (3) to determine customer expectation in term of computer's brand.